Psychohenic movement disorders. In relation to medical cases - Ventura, Roberto (2009)
This document is a work revision and an update of the psychogenic etiology of movement disorders’ literature. A medical case of dystonia psychogenia clinically established is reported, the medical history is analyzed from a neurological and psychiatric perspective, the positive diagnosis is explained, and the different diagnosis analyzed. Finally, we conclude the necessity of neuropsychiatric treatment when those patients suffer movement disorders.